A confessionalidade da educação: o ensino religioso na escola pública - Bonfá, Vanessa de Oliveira (2019)
Religious Education is the only subject included in the Brazilian Constitution of 1988, article 210, paragraph 1. Non mandatory, the subject composes the curricular matrix of the last year of Elementary School II cycle (9th year). Under the influence of the Catholic Church, the subject was inserted in the last Brazilian Magna Carta and LDB (1996), but it has been part of the education of this territory since its colonization. In the context of the European overseas expansion of the sixteenth century, the Catholic Church used this new space occupied by its followers a time when it was necessary to gain new church members. The colonies with their pagan natives were the main target of the institution. Based on these assumptions and intending to verify beyond the theoretical approach of study, the central objective of this research is to analyze how Religious Education operates in the state public schools, with a small focus in the municipal schools of Sao Jose do Rio Preto, SP, and how the law influences the format of the social classes. In addition to this purpose is toexpose the ideas of the secular state, illuminist ideals, and the debates generated in the press about the discipline after the approval of the denominational teaching by the STF in 2017. With a conservative approach, the Religious Teaching becomes another way of controlling the professional educator, once student demonstrations come into force in the middle, the teacher is soon pointed out as an incentive for such acts threatening the standards of conduct standardized by the conservative state.